An assessment of the intensity of extension-bending coupling and its effect on the stability of a thin laminate plate - Zaczynska, Monika; Fotovat, Mehdi Bohlooly; Kaluzna, Zuzanna (Bulletin of the Polish Academy of Sciences Technical Sciences, 2026)
The paper presents an investigation to find a method for assessing the intensity of extension-bending mechanical coupling in the behavior of thin plates. The analysis considers thin, simply supported square laminate plates subjected to in-plane compression. Plates with various plies stacking sequences with extension-bending coupling phenomenon were analyzed employing the finite element method software and using a developed closed-formed equation – the analytical method. The coupling intensity was quantified using two dimensionless stiffness reduction coefficients and a nondimensional anisotropic coefficient, known from literature. A reduction in the buckling load for plates with different layer arrangements, observed during nonlinear analysis, was used as a measure of coupling intensity. The results revealed that laminates with high extension-bending coupling intensity could exhibit up to 19% reduction in the buckling load. Additionally, the individual contributions of coupling intensity parameters to this reduction were identified. The validity of the proposed method was further evaluated for plates with different boundary conditions. These findings provide a foundation for predicting the behavior of mechanically coupled laminates without the need for extensive stability analysis.